Parent’s Perspectives: Collaborative Practice in Academic Services for Gifted Children - Suseno, Adi; Taslim, Patricia Lestari; Wahab, Rochmat (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2024)
Collaboration between teachers and parents in academic services for gifted children is important. The role of parents in collaboration is still often not optimized. This research aims to describe parents' perspectives on the practice of collaborative academic services for gifted children from the aspects of parental roles, forms of collaboration, and challenges in collaboration. This research used a survey involving 14 parents who were members of the Parents Support Group for Gifted Children (PSGCC) Yogyakarta community with the criteria of having gifted children and having experience collaborating with teachers or school officials. Data collection was carried out through a questionnaire that covered aspects of the role of parents, forms of collaboration carried out by parents, and challenges in implementation practice. Data were analyzed using a descriptive approach with percentage techniques. The research results show that parents play a significant role in meeting learning needs, assisting the learning process, and monitoring the development of gifted children. The most common form of communication is building communication forums intending to share information about the profile and condition of gifted children so that they get the right services. The challenge faced by parents is the limited understanding of teachers and qualified resources in the field of giftedness which has an impact on less than optimal academic services for gifted children. Therefore, collaboration from a parent's perspective can be a consideration in academic services for gifted children by increasing understanding of each other's roles, building communication forums, and mapping challenges that can be overcome collaboratively.